Barbed Sutures in Total Knee Arthroplasty: Are They Really Useful? A Randomized Controlled Trial - Gamba, Carlo; Hinarejos, Pedro; Serrano-Chinchilla, Paula; Leal-Blanquet, Joan; Torres-Claramunt, Raul; Sánchez-Soler, Juan; Monllau, Joan Carles (The Journal of Knee Surgery, 2019)
Bidirectional barbed sutures (BBSs) have recently been investigated in total knee arthroplasty (TKA). The contrasting results from the scarce literature suggest that BBSs are safe, save time and money, and give results comparable to traditional sutures. The purpose of the study is to test the real effect of BBSs on closure time in TKA and assess the functional results as well as the complications related to them. It was a randomized controlled trial. Eighty-five patients undergoing primary TKA were assigned to receive traditional closure with Vicryl (V-group) or with BBSs (Q-group). The exclusion criteria were significant coronal deformity, flexion contracture, or the need for stem and/or augmentation. The closure time for the capsule and that for the subcutaneous layer were registered separately. Intraoperative incidences were recorded. The follow-up was up to 1 month, during which the range of motion (ROM), superficial or deep infection, and wound dehiscence were assessed. There was a significant reduction in the capsule layer (27 seconds; p = 0.02) and global time closure (51 seconds; p = 0.01) in the Q-group. No differences were found in the subcutaneous layer (24 seconds; p = 0.055). There were more intraoperative suture breakages in the Q-group, mainly in the subcutaneous layer (p < 0.001). No differences in terms of dehiscence, infection, and ROM were observed at the 1-month follow-up. BBSs allow for slightly faster wound closure than Vicryl during a TKA. However, the differences observed have minimal clinical repercussions. Moreover, no differences in the infection rate (deep or superficial), dehiscence, or ROM were found.
Keywords: barbed suture; total knee arthroplasty; closure time